Human Resource Planning and organization performance of Bursa Saham Malaysia listed companies - Sofian, Bujang (2007)
This study investigates whether there are differences in organization performance between companies implemented human resource planning and not implemented human resource planning. The dependent variable is organization performance, which measured top management's perception on their organization financial performance. The survey was carried out randomly on public listed companies in the main board of Bursa Saham Malaysia. The results of the study suggest that there are significant differences of organization performance between companies implemented human resource planning and companies not implemented human resource planning.